Eksperimen Metode Contextual Teaching And Learning (CTL) Dan Discovery Learning (Dl) Dalam Pembelajaran Matematika Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Pada Siswa Kelas VIII Semester Genap SMP Negeri 1 Teras Tahun 2015/2016 - Faizah, Siti; , Idris Harta,MA.P.hd (2016)
The Research is conducted to know: (1) the contribution of CTL and DL methods toward the results of mathematics learning, (2) the contribution of student motivation degrees in learning toward the results of mathematics learning, (3) the interaction between the CTL, DL methods and learning motivation towards the result of mathematics learning. This type of research is an experimental research. The population is the students of class VIII SMP N 1 Teras in theyear 2015/2016. Samples from this study are three classes in totaling 96 students. VIIIF class as the first experimental class uses the CTL method, VIIIA class as the second experimental class uses the DL method and the class VIIIG as the control class uses Expository method. The sampling technique is cluster random sampling. Data collected by the test, questionnaire, and documentation. Data were analyzed using two-way analysis of variance with different cells. The results of the study at α = 0.05 conclude that: (1) there is contribution in learning with CTL and DL method stoward the results of mathematics learning with F_obs = 18.1492124>F_α = 3.10; (2) there is contribution of learning motivation degrees toward the results of mathematics learning with F_obs = 5.466034957>F_α = 3.10; (3) there is an interaction between the CTL, DL methods and motivation towards the result of mathematics learning with F_obs = 0.755458266 <F_α = 2.48. Keywords: results of learning, learning motivation, CTL & DL methods